IGNEM: Estrategia de visibilización y reflexión sobre la normalización de la violencia contra la mujer (2025)
In recent years, it has become clear that the role of women throughout history has not been fair, especially when it comes to respect for their bodies and understanding of their sexuality. Therefore, IGNEM was born, a creative audiovisual project to highlight the great mystery of the normalization of sexual harassment in sociocultural groups close to women. IGNEM was created so that people can come to understand the violence that women have been fighting for decades. A project that respects their history and reminds us that the struggle is not yet over.